Corporate dividend policy practices: perceptions of financial officers of listed companies in Colombo Stock Exchange - Kengatharan, L. (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
Main objective of this survey was to find out the perceptions of financial officers on dividend policy practices in Sri Lanka. Current survey further extended to examine whether firm characteristics influence the corporate dividend policy practices. Stratified random sampling was used to select the 150 participants from 20 different sectors in Colombo Stock Exchange (CSE). Primary survey was carried out to collect the data using structured questionnaire in 2017 and response rate was 20%. Cronbach' alpha was used to evaluate the reliability of the collected data. Data were analyzed by applying mean, percentage analysis and Chi-square test. Results of the survey revealed that financial managers believe that dividend payout ratio affects the market value of the firm, company willing to rescind dividend increase in the event of growth opportunities, company's dividend change follows shift in long term sustainable earnings, company focuses more on absolute level of dividends than dividend changes and dividends provide signaling mechanism of the future prospects of the firm. Therefore, it was observed from the perceptions of finance professionals that dividend decisions is one of the factor affect the market value of the firm. Results of the survey further expressed that the firms characteristics: market capitalization of the firms, types of industry, educational qualification and experience of financial officers are influencing the use of certain dividend policy practices in selected firms in this survey. The survey suggested that the dividend policy is considered as very important one to the financial officers and the potential investors as it is affecting the market value of the firms. Present survey just focused on beliefs of management on dividend policy rather studying the gap between beliefs on dividend policy of management and practical application on dividend policy. Further, it should be studied that how financial officers are working with the dividend policy in order to maximize the shareholders' wealth.
Keywords: dividends; dividend policy; perceptions; financial officers